S, Sosialisasi Sosialisasi Tinggi Muka Air Banjir Di Situ Wangi Kabupaten Ciamis: Tinggi Muka Air Banjir - Laksono Nugroho; Hanie Teki Tjendani; Esti Wulandari; Ony Frengky Rumiyin; Yeyen DAR; Nizam FZ (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
To enhance community preparedness against flooding, it is necessary to disseminate information on reservoir water levels to residents living around Situ Wangi in Hayawang Hamlet, Winduraja Village, Kawali District, Ciamis Regency, West Java Province. Such dissemination is intended to increase public awareness and preparedness in anticipating flood events around the reservoir, thereby minimizing the risk of loss of life and damage to infrastructure. The local community should be informed about the Normal Water Level (NWL) and the Flood Water Level (FWL) of the reservoir. Among these, the Flood Water Level is the most critical because it represents the maximum water level that may occur during flood events and poses the greatest potential hazard to surrounding areas. Therefore, a flood water level awareness and dissemination program is proposed for Situ Wangi, located in Hayawang Hamlet, Winduraja Village, Kawali District, Ciamis Regency, West Java Province. Field-based community outreach activities were conducted to increase public awareness regarding flood hazards at Situ Wangi, Ciamis Regency. Through these activities, local residents were able to observe the flood water level conditions directly, thereby improving their understanding of flood preparedness and the actions that should be taken during flood events. The outreach program involved field surveys carried out jointly with members of the surrounding community. Explanations were provided regarding the maximum flood water level elevation, and inundation maps corresponding to potential flood scenarios were presented. This approach is considered an important preventive measure to enable communities to anticipate flood events and reduce the potential impacts of flooding, including loss of life and damage to property and infrastructure. The results of the outreach activities indicated that the Normal Water Level (NWL) of Situ Wangi is at an elevation of +411.68 m, while the Flood Water Level (FWL) is at an elevation of +411.98 m. Keywords: Situ Wangi, Normal Water Level (NWL), Flood Water Level (FWL)